Pomegranate extract-loaded sphingosomes for the treatment of cancer: Phytochemical investigations, formulation, and antitumor activity evaluation. - Huda Jamal AlMadalli; Bazigha K Abdul Rasool; Naglaa Gamil Shehab; Francesca Della Sala; Assunta Borzacchiello (PLoS ONE)
Aim Formulation of Pomegranate Extracts (PE)-loaded sphingosomes as an antitumor therapy for the intravenous and passive targeted delivery to various tumor types, especially that of the breast, colon, and uterus; to increase the therapeutic activity and decrease the adverse effects profile. Methods The pericarp and seeds' juice of Punica granatum were each extracted using D.W. and ethanol. Phytochemical investigation of all extracts was carried out including total phenolics, flavonoids, and anthocyanins contents, the antioxidant activity, as well as HPLC analysis of phenolics and flavonoids. The antitumor potential of all extracts was also tested utilizing three cell lines: MCF-7, HeLa, and HCT116. The candidate extract was chosen for the formulation phase and was entrapped into the sphingosomes using the thin-film hydration method and employing three different PE: lipids weight ratios. The synthesized formulations were characterized for their size, morphological features, zeta potential, entrapment efficiency, and in vitro drug release and kinetics modeling studies. The optimized formula was further analyzed by FTIR spectroscopy and electron microscopy. The antitumor activity of F2 was also investigated using the same cancer cell lines compared to the plant extract. Results The highest phenolics, flavonoids, and anthocyanins contents were observed in the ethanolic pericarps extract (EPE), followed by the ethanolic seeds extract (ESE). Consequently, EPE showed a higher antitumor activity hence it was selected for the formulation phase. PE-loaded sphingosomes formula (F2) was selected for having the highest EE% (71.64%), and a sustained release profile with the highest in vitro release (42.5±9.44%). By employing the DDSolver, the Weibull model was found the most suitable to describe the PE release kinetics compared to other models. The release mechanism was found to follow Fickian diffusion. Simulated pharmacokinetic parameters have portrayed F2 as the candidate formula, with the highest AUC (536.095) and slowest MDT (0.642 h). In addition, F2 exhibited a significant (p>0.05) stronger and prolonged anticancer effect against MCF-7, HeLa, and HCT116 cell lines at all concentrations tested compared to the free extract. Conclusion The results proved that sphingosomes are an effective delivery system, improving pharmacological efficacy and reducing serious side effects of anticancer medications and natural products.